HIV/AIDS and Tuberculosis in Central Asia - Godinho, Joana; Novotny, Thomas; Tadesse, Hiwote; Vinokur, Anatoly (Washington, DC: World Bank, 2013)
The countries of Central Asia are still at the earliest stages of an HIV/AIDS epidemic. However, there is cause for serious concern due to: the steep growth of new HIV cases in the region; the established related epidemics of injecting drug use, sexually transmitted infections (STIs) and tuberculosis (TB); youth representing more than 40 percent of the total regional population; and the low levels of knowledge about the epidemics. The underlying causes for the interlinked epidemics of drug abuse, HIV/AIDS, STIs and TB in Central Asia are many, including drug production in Afghanistan and its distribution throughout the Former Soviet Union (FSU); unemployment among youth; imprisonment for drug use; overcrowding in prisons; and striking levels of poverty. HIV/AIDS and tuberculosis may have a potentially devastating effect on human capital, economic development, and health systems reform. In Russia, economic analysis has described the significant future impact on health and health systems if the concentrated epidemic in that country goes unchecked (Ruhl et al. 2002). The opportunity for prevention in low prevalence environments provides an imperative for action, because when HIV prevalence among high-risk groups reaches 20 percent or more, prevention is no longer possible and expensive treatment for AIDS and related opportunistic infections will overwhelm under funded health care systems such as those in Central Asia. Low prevalence, or nascent epidemics of HIV create little incentive for focused attention. However, through careful consideration of the potential for these epidemics to grow, the World Bank can help client countries incorporate effective prevention strategies into health systems development projects or into specific public health projects to address these infections.